Utilization Of Buton Asphalt Solid Waste (ASW) Waste Bitumen Extraction In Concrete - Aulia, Siti Aja; Ekaputri, Januarti Jaya (Universitas Islam Sultan Agung, 2024)
Indonesia has 650 million tons of Buton Rock Asphalt (Asbuton) deposits. The mineral residue, known as Asphalt Solid Waste (ASW). The extraction left ASW by 65-90% of asbuton’s weight. However, 770 thousand tons/year of ASW remain underutilized, causing environmental pollution due to its hydrocarbon content. Based on XRD results, Asbuton minerals were dominated with 46% CaCO3, which are potential as a subtitute material in concrete. However, its hydrocarbon content at 68,911 ppm raises concerns. To prevent ASW hydrocarbons from contaminating concrete, solidification was attempted. This study investigates solidification by making Artificial Coarse Aggregate (ACA) products and using ASW as a subtitute for gravel in concrete. The ACAs were produced from a mixture of ASW and cement, molded into 50 x 100 mm cylinders, crushed after twenty eight-days moist curing, and tested according to ASTM C33 standard of gravel. ASW replaced 0-12.5% by volume of sand and ACA replaced 0-12.5% by volume of gravel in concrete with a target compressive strength of 45 MPa at twenty eight-days. Heat of hydration and shrinkage were tested to indentify the impact of CaCO3 from ASW on concrete. The results showed that ACA could reduce 9% of ASW hydrocarbons. However, the ACA produced did not meet the gravel standard in ASTM because ACA absorption reached 6.75% and abrasion test up to 57%. Neverthless, ASW’s high absorption reduced heat hydration by 10% and shrinkage by 83% compared to normal concrete.